Twenty-Fourth Meeting of Consultation of Ministers of Foreign Affairs - de los Estados Americanos, Organización (2016)
The Twenty-Fourth Meeting of Consultation of Ministers of Foreign Affairs in the Organization of American States, on September 21, 2001, acting as a consultative body in application of the Reciprocal Assistance Exchange Treaty (TIAR), considering the terrorist attacks perpetrated against innocent people from different countries that took place on September 11, 2001 in the territory of the United States of America.